Israeli teachers make sense of global citizenship education in a divided society- religion, marginalisation and economic globalisation. Issue 2 (3rd April 2019) - Goren, Heela; Maxwell, Claire; Yemini, Miri
ABSTRACT: Global citizenship education (GCE) has recently been promoted by national education systems and supranational organisations as a means for facilitating social cohesion and peace education. We examined the perceptions of GCE held by teachers from the three main education sectors in Israel: secular-Jewish, religious-Jewish, and Palestinian Arab, and found stark differences in the way teachers from each sector interpreted the term. For marginalised groups (Palestinian Arab), GCE is seen as offering a way of securing a sense of belonging to a global society. For already well-resourced social groups (Jewish secular), GCE is viewed as a way of promoting global futures. Meanwhile, for the Jewish religious minority in Israel, GCE is seen as a threat to national identity and religious values. Our findings cast doubt on the unifying potential of GCE, and we conclude by calling upon scholars and policymakers to examine unique obstacles facing GCE in their various contexts.